Good University Governance: A Consensus of Higher Education Ideology? - R. A. Widyanti Diah Lestari; Irianto , Gugus; Roekhudin (Accounting Department,, 2024)
Objective — This study aims to reconstruct the concept of Good University Governance so that it is free from the hegemony and domination of neoliberalism, which is promoted through the concept of New Public Management. Design/methodology/approach — Problem-solving in this study will use the Critical Paradigm, by applying the Pancasila ideology as a tool for solving problems. Pancasila as the original ideology of Indonesia is used as an effort to counter-hegemony and domination of ideological consensus that occurs as a result of false awareness created and disseminated through universities. Findings — Researchers developed the concept of Good University Governance (GUG) based on Pancasila as an attempt to counter the hegemony and domination of neoliberalism in the field of higher education governance. Using four domains namely General Characteristics, Funding, Research, Leadership, and Academic Staff Pancasila as the original ideology of the Indonesian nation as a tool for the restoration of praxis GUG so that it becomes a more ideal GUG. Practical Implications — This study emphasizes the importance of the original ideology of the Indonesian nation as a tool to carry out counter-hegemony actions on the ideological consensus that has occurred in a society that has been assimilated due to false consciousness indoctrinated by neoliberalism in the field of higher education. Originality/value — This study cites the essence of the theory of hegemony from critical thinker Gramsci as an entry point to understanding various inequalities that occur in the field of education. The Pancasila ideology is used as a critical analysis tool, to fight the hegemony of ideological consensus that occurs as a result of false consciousness created and disseminated through educational means. Through a critical approach, researchers want to understand how neoliberalism practices domination and hegemony in the field of higher education management, giving rise to false consciousness in society. In this way, researchers can develop this concept as an effort to fight against existing hegemony in the field of higher education governance, namely using Pancasila as the original ideology of the Indonesian nation. The GUG concept based on Pancasila is grouped into four domains, namely General Characteristics, Funding, Research, Leadership, and Academic Staff. Keywords: GUG, Pancasila ideology, Hegemony Theory, False-consciousness, New Public Management. Research Papers: Types of Paper.